Intramammary Immunisation Provides Short Term Protection Against Mannheimia haemolytica Mastitis in Sheep - Tassi, Riccardo; Schiavo, Martina; Filipe, Joel; Todd, Helen; Ewing, David; Ballingall, Keith T. (Frontiers in Veterinary Science, 2021)
Mastitis affects both dairy and meat/wool sheep industries with losses due to reductions in milk quality and quantity, increased treatment costs and restricted lamb growth. Effective vaccines would be important tools for mastitis control. However, the development of vaccines against mastitis has proved challenging due to the failure to target protective immunity to the mammary gland. In order to target responses to the mammary gland, this study tested whether local administration directly into the gland through the teat canal or in the udder skin confers protection against an intramammary infection. In this study, we tested a vaccine that confers protection against respiratory disease caused by Mannheimia haemolytica to determine if it also protects against intramammary infection by the same organism. No evidence of protection was observed in animals that received a subcutaneous immunisation in the udder skin, however, intramammary immunisation provided almost complete protection against an experimental challenge administered seven days post immunisation but not if the challenge was delivered 14 days post immunisation. To investigate further the nature of this variation in response, the somatic cell count and concentration of cytokines Interleukin-1β, Interleukin-10 and Interleukin-17A was determined in milk over the course of each study. Intramammary immunisation induced an inflammatory response within the mammary gland, characterized by increases in SCC and in the production of cytokines IL-1β, IL-10 and IL-17A. This response was similar to that observed in un-vaccinated control animals post challenge. The SCC and cytokine levels had returned to levels comparable with un-vaccinated controls prior to challenge at both seven and 14 days post immunisation. Therefore, the protective effect observed seven days post immunisation is unlikely to be purely a result of the inflammatory response induced by the vaccine. Further studies are ongoing to determine the nature of the response in the mammary gland following intramammary immunisation.